Health facility readiness, facilitators, and implementation challenges of package of essential non-communicable disease program in selected municipality of Lalitpur district: a mixed method study - Rimal, Saroj; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: The global burden of non-communicable diseases constitutes a major public health challenge as well as a serious threat to social and economic development. The Nepal package of essential non-communicable disease (PEN) began in October 2016 with two pilot districts. The program was expanded to 77 Districts of Nepal by the year of 2021.The Program covers major NCDs like cardiovascular disease (CVD), diabetes, cancers (Breast and Cervical) and chronic respiratory diseases. This study assessed its sta-tus in Lalitpur district, Nepal. Aim of the study was to assess the health facility readiness, facilitators and implementation challenges of PEN program.Method: A cross-sectional design with concurrent triangulation mixed meth-od was used. All the primary government health facilities of Lalitpur metropolitan city and Mahalaxmi municipality were included in study. Duration of the study was one month. Readiness for PEN program was assessed using pre-validated tools. By using purposive sampling for qualitative data and it was analyzed by using Braun and Clarke’s six steps thematic analysis.Result: The overall readiness index for PEN services was 2526(71.4%) but it was less than 70%(not read) in Lalitpur metropolitan city and more than 70% in the Mahalaxmi municipality. Nearby tertiary hospital, positive leadership and availability of medicines were identified as facilitators while lack of trained health workers, unavailability of equipments and essential medicines were considered as major implementation challenges for the program.Conclusion: Despite of 71.4% overall readiness for PEN services, disparities exist between municipalities. Facilitators such as nearby tertiary hospital and positive leadership contrast with challenges like a shortage of trained health workers and essential supplies. Addressing these disparities and challenges is crucial for successful implementation of PEN program.